Lexical Development in Young Children With Autism Spectrum Disorder (ASD): How ASD May Affect Intake From the Input - Arunachalam, Sudha (J Speech Lang Hear Res, 2018)
PURPOSE: Most children with autism spectrum disorder (ASD) have below-age lexical knowledge and lexical representation. Our goal is to examine ways in which difficulties with social communication and language processing that are often associated with ASD may constrain these children's abilities to learn new words and to explore whether minimizing the social communication and processing demands of the learning situation can lead to successful learning. METHOD: In this narrative review of recent work on lexical development in ASD, we describe key findings on children's acquisition of nouns, pronouns, and verbs and outline our research program currently in progress aimed at further elucidating these issues. CONCLUSION: Our review of studies that examine lexical development in children with ASD suggests that innovative intervention approaches that take into account both the social communication and processing demands of the learning situation may be particularly beneficial. PRESENTATION VIDEO: https://doi.org/10.23641/asha.7324013